Kodifikasi dan Efektivitas Kebĳakan Fiskal untuk Menurunkan Emisi Gas Rumah Kaca pada Industri Semen, Baja dan Pulp - Joko Tri Haryanto; Berly Martawardaya (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2015)
Industrial activity is known as one of the major contributors of greenhouse gas emissions (GHG). Sources of GHG emissions from the industrial sector include energy inputinput, the inputinput of non-energy, industrial processes and industrial waste. Thus, the industrial sector, listed as one of the important sectors in the National Action Plan (NAP) Reduction of GHG emissions. Implementation of mitigation actions in the industrial sector clearly requires appropriate regulatory framework. The right combination of policy and fiscal instruments needed to encourage industry players become actively involved in the national eﬀort to reduce GHG emissions in Indonesia. The problem, the need for coordination regulations related eﬀorts to reduce GHG emissions in the industrial sector of each Ministry / Institutions (K / L) are associated in particular Ministry of Finance Regulation (PMK and the Regulation of the Minister of Industry (Permenindustri). For that study was conducted using the framework regulatory analysis for the creation of regulatory coordination between the PMK and Permenindustri. Through the codification mechanism, expectedd to increase the eﬀectiveness of fiscal policy to reduce GHG emissions in the industrial sector.